Neonatal jaundice and breastfeeding - Barbosa , Bruna Kelly Rocha; Queiroz, Carol Monique de; Macêdo, Caroline Ribeiro de; França, Danilo de Almeida; Lima, Fernanda Gabrielle Pinto Salvador de; Oliveira, Sabrina Gomes de (Seven Editora, 2023)
Neonatal jaundice is defined by a yellowish discoloration of the skin, conjunctiva, and sclera due to elevated serum or plasma bilirubin in the neonatal period. In most newborns it is an ephemeral, low-severity event. This event can be triggered, for example, by ABO and Rh factor incompatibility, glucose-6-phosphate dehydrogenase (G6PD) deficiency, and immaturity of liver metabolism processes. However, breastfeeding-associated neonatal jaundice stems from two different mechanisms: the direct effect of mature human milk inducing increased intestinal reabsorption of bilirubin and jaundice resulting from inadequate intake of human milk. DOI:https://doi.org/10.56238/alookdevelopv1-101